PENGARUH TERAPI MUSIC MOZART TERHADAP NYERI MUSKULOSKELETAL PADA LANSIA DI POLI GERIATRI RSUD KOTA PRABUMULIH - Sanniyah Mei Sanyana; Mujahidin; Yunita Liana; Abu Bakar Sidika (Jurnal Kesehatan dan Pembangunan, 2026)
Musculoskeletal pain is a common complaint among the elderly and can affect functional ability and quality of life. Elderly individuals experiencing musculoskeletal pain tend to have limitations in daily activities, impaired mobility, and decreased independence. One non-pharmacological intervention that can be used to reduce pain is Mozart music therapy, which provides relaxation and distraction effects that help decrease pain perception. This study aimed to determine the effect of Mozart music therapy on musculoskeletal pain in elderly patients at the Geriatric Clinic of RSUD Kota Prabumulih. This study employed a pre-experimental design with a one-group pretest–posttest approach. The sample consisted of 30 elderly respondents selected using purposive sampling. Pain intensity was measured before and after the administration of Mozart music therapy using a pain scale. Data were analyzed using the Wilcoxon Signed Rank Test. The results showed a Z value of ?4.243 with a significance value of Asymp. Sig. (2-tailed) = 0.000 (p < 0.05), indicating a significant difference between pain intensity before and after Mozart music therapy. These findings suggest that Mozart music therapy is effective in reducing musculoskeletal pain among the elderly. In conclusion, Mozart music therapy has a significant effect on reducing musculoskeletal pain in elderly patients, and it can be considered an effective non-pharmacological nursing intervention for pain management in geriatric patients.